2022
DOI: 10.1186/s12870-022-03537-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and transcriptome analyses identify the plant immunity systems that facilitate sesquiterpene and lignan biosynthesis in Syringa pinnatifolia Hemsl.

Abstract: Background Syringa pinnatifolia Hemsl. is a shrub belonging to the Oleaceae family. The peeled woody stems and roots of S. pinnatifolia are used in Chinese traditional medicine. This plant has been used for centuries, and modern pharmacological research has revealed its medicinal value. However, the wild populations of S. pinnatifolia have been decreasing, and it has been listed as an endangered plant in China. To elucidate the molecular mechanism leading to the synthesis of the major component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…The 1 H-and 13 C-NMR data (Tables 1 and 2) showed high similarity to 2. Analysis of the spectroscopic data showed the presence of a sp 3 (Δδ C + 82.1), and further corroborated by the observed HMBCs from H-1' to C-3' and C-5', thus establishing its planar structure. NOESY correlations between H 3 -13 and H 3 -13', along with those of H 3 -13'/ H 3 -15 and H 3 -13/H 3 -15, revealed these protons were co-facial (Figure 5).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The 1 H-and 13 C-NMR data (Tables 1 and 2) showed high similarity to 2. Analysis of the spectroscopic data showed the presence of a sp 3 (Δδ C + 82.1), and further corroborated by the observed HMBCs from H-1' to C-3' and C-5', thus establishing its planar structure. NOESY correlations between H 3 -13 and H 3 -13', along with those of H 3 -13'/ H 3 -15 and H 3 -13/H 3 -15, revealed these protons were co-facial (Figure 5).…”
Section: Resultssupporting
confidence: 56%
“…[1] The peeled roots, stems, and twigs have long been used as a traditional Mongolian medicine in local for treating cardiovascular symptoms, asthma, pain, and fever. [2] Although listed as one of the third-level national endangered plants in China, [3] SP is attracting attention from researchers because of its well-known clinical efficiency in Inner Mongolia and anti-acute myocardial infarction effect in modern research. [4 -9] Previous studies revealed that terpenoids in particular sesquiterpenoids are the most representative constituents of SP, [10 -14] and more than 10 types of sesquiterpenoids have been described from SP so far, including humulane, eremophilane, caryophyllane, and pinnatane, which are specific constituents used to distinguish SP from other Syringa species.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid also enhances the resistance to drought stress [ 41 ]. In addition, lignin is the main component of the cell walls of vascular plants; it promotes lignification and enhances the ability of plants to resist stress, such as enhancing the resistance of Zea mays to leaf blight and gray spot [ 32 , 42 ]. Melatonin acts as the first line of defense against oxidative stress in the internal and external environments.…”
Section: Discussionmentioning
confidence: 99%
“…For volatile metabolome analysis of calli samples, the headspace–solid-phase microextraction–gas chromatography–mass spectrometry method was used, as previously described. [6]…”
Section: Methodsmentioning
confidence: 99%